PENGALAMAN HIDUP PASIEN PASKA STROKE DI SUMATERA BARAT TAHUN 2017 - Pratama, Engla Rati (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Patients with stroke in Indonesia is increasing every year and experiencing variousphysical disorders, psychological disorders, communication disorders, and cognitiveimpairment. The experience felt by post-stroke patients varies depending on the conditionof each individual. The purpose of this study was to explore the life experiences of poststrokepatients. This research was conducted in Bukittinggi City and its surrounding areafrom 20 October to 20 November 2017. The research type is qualitative research withphenomenology study. Participants were taken based on purposive sampling whichamounted to 7 people based on the inclusion criteria; post-stroke patients who have gonethrough 6 months of stroke, no speech impairment, and mild to moderate degree of stroke.Data from the participants in the analysis using the Collaizi analysis technique. The resultsof the research were 5 themes: 1) The perceived response to post-stroke conditionchanges; 2) Inner power as a source of strength; 3) Efforts to overcome illnesses byundergoing medical and traditional medicine; 4) Family Support; 5) Sexual response feltby post-stroke patients. It is expected that nurses in hospitals and other healthcare serviceswill be able to improve health education on stroke-related diseases for patients andfamilies and address psychosocial problems by providing life-nursing therapy such assupportive therapy, cognitive therapy, cognitive behavioral therapy, thought stoppingtherapy, and family psychoeducation